SOCIODEMOGRAPHIC AND CLINICAL PROFILE OF TUBERCULOSIS TREATMENT DROPOUT CASES IN BRAZIL (2015-2024) (REMUNOM, 2026)
Quantitative, retrospective, and descriptive-analytical study, conducted using secondary data from the Brazilian Notifiable Diseases Information System (SINAN), aiming to analyze tuberculosis treatment abandonment in Brazil from 2026 to 2024. Among the analyzed cases, the category new case predominated (64.0%), followed by re-entry after abandonment (26.4%), which was considered a key category due to the high recurrence of the outcome. A higher prevalence of treatment abandonment was observed among individuals who did not undergo Directly Observed Treatment (DOT), with a proportion of 20.1%, compared to those who received DOT (8.6%), yielding a prevalence ratio of 2.34 (95% CI: 2.31–2.38; p